Chemokines in Renal Diseases - Stephan Segerer; Peter J. Nelson (The Scientific World Journal)
The chemokines, members of a large family of chemotactic cytokines, act as directional cues for sorting inflammatory cell subsets to sites of inflammation or lymphoid microenvironments. In addition to their effects on migration, chemokines can also activate effector function in leukocytes and are involved in cell proliferation and angiogenesis. Therefore, it is not surprising that chemokines play important roles in a wide range of human diseases, including genetic immunodeficiencies, infections, autoimmune diseases, and malignant tumors. In this report, we have reviewed recent developments (since mid 2003) in chemokines in renal diseases. In animal models, chemokines are produced at the site of injury, leading to inflammatory cell recruitment. The therapeutic impact of the blockade of CCR1, CCR2, CCR4, CCR5, or the corresponding ligands has been further studied in various renal disease models. Recent studies on the role of the chemokine receptors in human diseases have demonstrated the expression of CXCR1, CXCR3, CCR2, and CCR5 on different subsets of inflammatory cells. The number of CCR5- and CXCR3-positive interstitial infiltrating cells (mainly T cells) correlates with renal function and proteinuria in glomerular diseases. Polymorphisms of chemokines and chemokine receptors are of impact on renal disease courses and allograft survival. Chemokine receptor blockade has approached clinical applications in nonrenal diseases and awaits the application in patients with kidney diseases.